2019
DOI: 10.1073/pnas.1820541116
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of fear generalization by the zona incerta

Abstract: Fear expressed toward threat-associated stimuli is an adaptive behavioral response. In contrast, the generalization of fear responses toward nonthreatening cues is a maladaptive and debilitating dimension of trauma-and anxiety-related disorders. Expressing fear to appropriate stimuli and suppressing fear generalization require integration of relevant sensory information and motor output. While thalamic and subthalamic brain regions play important roles in sensorimotor integration, very little is known about th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…It is well-demonstrated that PVT serves as a major thalamic interface between hindbrain and hypothalamus, and is also involved in hypothalamic–thalamic–striatal circuitry for integrating appetitive motivation with energy state and feeding 35 , 45 . A recent study shows that PVT receives GABAergic inputs from ZI, a brain region that modulates defense and fear behaviors 46 , 47 , and activation of ZI GABAergic inputs to PVT induces rapid binge-like feeding 38 . In a sharp contrast to the orexigenic feeding effect of GABAergic inputs to PVT, our results show that VMH SF1 neurons project excitatory glutamatergic inputs to PVT to inhibit food intake.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-demonstrated that PVT serves as a major thalamic interface between hindbrain and hypothalamus, and is also involved in hypothalamic–thalamic–striatal circuitry for integrating appetitive motivation with energy state and feeding 35 , 45 . A recent study shows that PVT receives GABAergic inputs from ZI, a brain region that modulates defense and fear behaviors 46 , 47 , and activation of ZI GABAergic inputs to PVT induces rapid binge-like feeding 38 . In a sharp contrast to the orexigenic feeding effect of GABAergic inputs to PVT, our results show that VMH SF1 neurons project excitatory glutamatergic inputs to PVT to inhibit food intake.…”
Section: Discussionmentioning
confidence: 99%
“…In a perhaps related manner, in rodent studies, the rostral ZI provides inhibitory control over the thalamus during sleep (Llinás & Jahnsen, 1982;Watson et al, 2014), which may also relate to its perceived role in modulating consciousness (Mitrofanis, 2005;Power & Mitrofanis, 2001). Finally, recent evidence, also in rodents, suggests an important role for the ZI in modulating fear generalization (Venkataraman et al, 2019) and appetite (Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…In this case, the CS− becomes what is known as a "safety signal." This paradigm has been used successfully in both rat (Duvarci, Bauer, & Pare, 2009) and mouse models (Venkataraman et al, 2019).…”
Section: Differential (Discriminative) Fear Conditioningmentioning
confidence: 99%
“…Increasing the intensity of the US is one of the most reliable parameters for promoting generalized responding. Numerous studies have shown that increasing the intensity of the US increases generalization (Baldi, Lorenzini, & Bucherelli, 2004;Ghosh & Chattarji, 2015;Venkataraman et al, 2019). For instance in mice, "weak" US intensities from 0.3 to 0.5 mA results in CS+ discrimination, while 0.8-to 1.0-mA US intensity promoted generalization (Ghosh & Chattarji, 2015).…”
Section: Extrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation